Kebijakan Publik dan Ketimpangan Akses Pendidikan Digital pada Masa Pasca Pandemi Covid-19 - Maharani, Nabila Putri; Saputra, Roni (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2025)
The post-COVID-19 pandemic period has marked an acceleration in the adoption of digital education through distance and hybrid learning policies. However, this acceleration has also revealed persistent inequalities in access to digital education across socioeconomic groups. This article analyzes the role of public policy in shaping inequalities in access to digital education in the post-pandemic period. The study examines empirical evidence from international and comparative literature on digital education policies, the gap in technology access, and their implications for educational equity. The analysis shows that policies focused on expanding digital platforms without supporting infrastructure, digital literacy, and protecting vulnerable groups tend to reinforce educational exclusion. Low-income households, areas with limited connectivity, and educational institutions with low fiscal capacity face multiple barriers to accessing quality digital learning. This article emphasizes that post-pandemic public policy needs to shift from an emergency approach to structural policies oriented toward equitable access and quality. Integration of education, telecommunications, and social protection policies is a prerequisite for sustainably reducing inequalities in digital education.